DATA BARU TENTANG KAMPUNG KAUMAN YOGYAKARTA STUDI BERDASARKAN TEMUAN ARTEFAKTUAL - Chawari, Muhammad (Berkala Arkeologi, 2017)
Kauman is one of the oldest settlement and part of the bureaucratic structure of Yogyakarta's palace. The old buildings in Kauman were interesting topics to many research there. Mean while on the other hand, artifacts as anothersupporting data of the daily life there have never been revealed. This paper aims to look at the connection between the artifacts findings with the Kauman settlement as well as Yogyakarta's palace. Analytical descriptive method is used to describe and analyze the artifacts to see the development of Kauman itself.